1988
DOI: 10.3758/bf03197760
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and judgment as indicators of sensitivity to covariation of continuous variables

Abstract: The present study used both judgments of strength of relationship and measures of the ability to predict one variable from another to assess subjects' sensitivity to the covariation of two continuous variables. In addition, one group of subjects judged strength of relationship after merely observing the presentation of 60 pairs of two-digit numbers, and a second group made strength judgments after being actively engaged in predicting one member of a pair when given the other. The prediction and judgment data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…With few exceptions (see Well, Boyce, Morris, Shinjo, & Chumbley, 1988), studies concerned with human contingency judgments have involved binary variables. In the simplest case, there are only two binary variables.…”
Section: Contingency-judgment Tasksmentioning
confidence: 99%
“…With few exceptions (see Well, Boyce, Morris, Shinjo, & Chumbley, 1988), studies concerned with human contingency judgments have involved binary variables. In the simplest case, there are only two binary variables.…”
Section: Contingency-judgment Tasksmentioning
confidence: 99%
“…Jennings et al (1982) showed that individuals tend to underestimate low correlations between variables and that they only detect very high correlations (r Ͼ .8) with certainty. Well, Boyce, Morris, Shinjo, and Chumbley (1988) found that, although participants gave poor global judgments of strength of relationship, they were more accurate in predicting one variable from another. Using a prediction task, Malmi (1986) found that participants responded adequately to positive correlations in the data but showed a virtual lack of sensitivity to negative correlations.…”
mentioning
confidence: 92%
“…The majority of research has required participants to estimate the strength of the relationship between two dichotomous variables. In contrast, the few studies that have examined numerical stimuli (i.e., perceived covariation between continuous or 591 ordinal variables) have reported relatively accurate perceptions of covariation (e.g., Alloy & Tabachnik, 1984;Baumgartner, 1995;Bettman, Creyer, John, & Scott, 1988;Lane, Anderson, & Kellam, 1985;Malmi, 1986;Wainer & Thissen, 1979;Well, Boyce, Morris, Shinjo, & Chumbley, 1988;Wright & Murphy, 1984). The experiments that follow were restricted to the case of numerical stimuli.…”
mentioning
confidence: 99%